Analysis of Teaching Material Needs Based on a Contextual Approach Use Liveworksheet on Dynamic Fluid Materials - Fadhilla, Ririn; Satria Dewi, Wahyuni (Jurnal Pendidikan Tambusai, 2023)
This research aims to identify the needs of teachers and students in a material-based approach to learning physics at SMA Negeri 2 Padang. The current teaching materials are general and less interesting for students. The study uses a contextual approach to analyze material and present learning more meaningful and relevant to students' real lives. A questionnaire and journal analysis were conducted with 68 students and one teacher in high school Negeri 2 Padang. The results showed that learning is still teacher-centered and there is no special approach to overcome students' problem-solving abilities. There is also no integrated teaching materials yet, and the study suggests that materials need to be developed to develop a teach-based approach contextually using Liveworksheets on fluid dynamic materials.